A Solar Fresnel Collector Based on an Evacuated Flat Receiver. (November 2016) - Pauletta, Stefano
Abstract: Fresnel solar collectors constitute one of the types of line-focus collector systems which have been adopted worldwide for solar power production: ground-mounted mirror strips follow the sun to concentrate its rays onto a fixed receiver. Its constructive simplicity offers advantages which balance the loss in aperture efficiency and concentration ratio when compared to the Parabolic Trough technology. This article presents the design of a Linear Fresnel concentrator equipped with the flat evacuated solar collector developed at CERN and industrially manufactured in Valencia (Spain). The Flat Receiver Linear Fresnel concentrator has been optically modelled using a ray trace code and optimized trough Taguchi method applied to the annual solar yield of a solar power plant installed in Cairo. Available costing data on the typical CSP electricity generation island and on multi-effect desalination technology has then been adopted for the estimation of the levelized cost of electricity and co-produced fresh water.